2016
DOI: 10.1371/journal.pone.0150251
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transcriptional Signatures in Response to Listeria monocytogenes Infection Reveals Temporal Changes That Result from Type I Interferon Signaling

Abstract: Analysis of the mouse transcriptional response to Listeria monocytogenes infection reveals that a large set of genes are perturbed in both blood and tissue and that these transcriptional responses are enriched for pathways of the immune response. Further we identified enrichment for both type I and type II interferon (IFN) signaling molecules in the blood and tissues upon infection. Since type I IFN signaling has been reported widely to impair bacterial clearance we examined gene expression from blood and tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
(75 reference statements)
1
9
0
Order By: Relevance
“…Strain 10403s appeared to be the more potent stimulator of miR-155, perhaps due to greater induction of Tnf (Figure 9D ). Genes strongly associated with Type I IFN-response in L. monocytogenes infected macrophages and mice, Ifit3 and Mx1 , were also upregulated in infected SIM-A9 cells (Figure 9E ) ( 59 , 62 ). These results show L. monocytogenes infection of microglia upregulates miR-155 and markers of Type I IFN activation that are also upregulated at 3 d p.i in vivo .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Strain 10403s appeared to be the more potent stimulator of miR-155, perhaps due to greater induction of Tnf (Figure 9D ). Genes strongly associated with Type I IFN-response in L. monocytogenes infected macrophages and mice, Ifit3 and Mx1 , were also upregulated in infected SIM-A9 cells (Figure 9E ) ( 59 , 62 ). These results show L. monocytogenes infection of microglia upregulates miR-155 and markers of Type I IFN activation that are also upregulated at 3 d p.i in vivo .…”
Section: Resultsmentioning
confidence: 96%
“…(Figure 5 ). Upregulation of Ifit3 and Oas1 show a key role for stimulation by Type I IFN ( 59 ). Numbers of expressed transcripts were largely similar in B6.WT and B6.miR-155 −/− mice at 3 d p.i.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Listeria is a facultative intracellular pathogen that can infect both phagocytic and nonphagocytic cells, such as epithelial cells. In contrast to the numerous reports of global transcriptional changes induced by Listeria in host cells during infection ( 7 14 ), only few studies reported post-transcriptional alterations of host protein abundance ( 15 19 ). These studies focused on specific host proteins ( i.e.…”
mentioning
confidence: 83%